Epidigmatic Function of the English Numerals - Shvachko, Svitlana Oleksiyivna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article in question considers the functioning of quantitative units, their language and speech aspects. The research focuses upon the major items of the paper – definition of numerals, words of weight and measure, aims, methods of investigation, empiric material applied, evolution modifications, and perspectives of further study. Topicality of the paper is determined by the modern tendencies of today’s methodology, by the great interest of the linguists to the questions of self-determination. The paper in question modulated the parameters of the English lexico-semantic field of quantity. The hypothesis is being verified: words with common semes are opened to alike modifications (in our case words of number on the one hand, and words of weight and measure on the other hand).